Starting at the beginning : laying the foundation for lifelong mental health - Hodes, Matthew; Gau, Susan Shur-Fen; De Vries, Petrus J. (Academic Press, 2020)
"Starting at the Beginning: Laying the Foundation for Lifelong Mental Health coincides with the 24th International Association for Child and Adolescent Psychiatry and Allied Professions (IACAPAPA) Congress in Singapore, June 2020. This book examines the determinates of individual differences in children and young people, along with the origins of maladjustment and psychiatric disorders. It addresses the ways in which interventions and mental health services can be developed and shaped to address individual differences among children. Additional topics include environmental hazards and mental health and cultural psychiatry as a basic science for addressing mental health disparities. Chapters dive deeper into anxiety disorders in infants, gaming disorder, the pitfalls of treatment in OCD, and ADHD developmental neuropsychiatry. Another targeted section focuses on policies for child and adolescent mental health, including a review of mental health services in China, Oceania and East Asia"--